(untitled) (International Journal of Engineering and Computer Science, 2014)
This work is an extension of our previous work on task scheduling of a Distributed Computing Software in the presence of faults [2] in which an attempt was made to identify the task scheduling algorithms used for distributed environments that perform well in the presence of faults due to network failure or processor failure in the distributed system. In this paper we give some extensive results for identifying the task scheduling algorithms that perform well in the presence of communication and computation faults present in some special task graphs like systolic array task graphs, Gaussian elimination task graphs, Fast Fourier transform task graphs, and divide-and-conquer task graphs which can represent the distributed software. For our study we have selected six task scheduling algorithms. We have compared these algorithms using three comparison parameters like normalized schedule length, number of processors used and average running time, and evaluated them on the above mentioned task graphs in the presence of communication and computation faults. It is further evaluated under random and constant fault delays.